Numerical study of the water-sediment regulation scheme (WSRS) impact on suspended sediment transport in the Yellow River Estuary - Jia, Wenfei; Yi, Yujun (Frontiers in Marine Science, 2023)
The transport of suspended sediment plays an important role in regulating erosion-accretion in estuaries. The Yellow River, the second longest river in China, which has a large amount of sediment and contributes sediment to the Yellow River Estuary (YRE) every year. The water and sediment discharge patterns in the lower reaches of the Yellow River have experienced significant changes over recent decades. In particular, the water-sediment regulation scheme (WSRS) of the Xiaolangdi Reservoir transports large amounts of water and sediment to the YRE within a very short time, causing dramatic changes in the spatiotemporal estuarine sediment dynamics. In this study, we presented a coupled numerical model based on FVCOM-SWAVE-SED that considered the highly dynamic sediment variations in the YRE. The sediment distribution and erosion-accretion patterns in the YRE during the WSRS in 2013 were analyzed by the high-resolution model. We also examined the effects of the main external driving forces (such as waves, tides, and runoff) on the sediment distribution and showed that runoff, tides, and waves were the key factors affecting the sediment distribution of the YRE. The sediment entering the YRE spread with freshwater, forming a high sediment concentration zone near the river mouth, where most of the sediments were deposited. The sediment dispersal distance was limited by the tidal shear frontal (TSF), and the southeast outspread length of the sediment was slightly larger than the northwest spread. Outside of the YRE, the areas with high flow currents exhibited high erosion.